Effects of musculoskeletal pain on sleep disorder and quality of life in school aged children who are new to sports - Fatma Kizilay; Burak Bugday (ROL Spor Bilimleri Dergisi)
Children who are new to sports may experience unusual physical stress, which may lead to musculoskeletal pain. The presence of pain may impair sleep and quality of life in children in varying age groups. Therefore, effects of musculoskeletal pain on sleep disorder and quality of life in younger and older school aged children who are new to sports investigated in this study. The study is conducted on children between 6-16 ages who are new to sports. Sociodemographic and sport-specific characteristics was questioned with a 10-question case form, sleep disorders were questioned with the Sleep Disturbance Scale for Children, and quality of life evaluated using the Pediatric Quality of Life Inventory. It was determined that 68% of the children starting to swimming had a musculoskeletal pain, and shoulder pain was the most common pain (30%). There was a statistically significant relationship between pain severity, quality of life, and sleep disturbance scores (p<0.05). There was a significant difference in sleep disturbance scores between younger children and older children (p<0.05). Sleep disturbance was observed less frequently in older children than in younger children. It was concluded that musculoskeletal pain is frequently experienced in children who are new to swimming sport, the pain is most common in the shoulder region, less frequently in the elbow, knee, back, and waist regions, and the presence of pain adversely affects sleep and quality of life in children. It was concluded that participation in sports at an early age may be a risk factor for sleep disorders.